2015
DOI: 10.1103/physrevlett.115.168101
|View full text |Cite
|
Sign up to set email alerts
|

Propulsion and Instability of a Flexible Helical Rod Rotating in a Viscous Fluid

Abstract: We combine experiments with simulations to investigate the fluid-structure interaction of a flexible helical rod rotating in a viscous fluid, under low Reynolds number conditions. Our analysis takes into account the coupling between the geometrically nonlinear behavior of the elastic rod with a nonlocal hydrodynamic model for the fluid loading. We quantify the resulting propulsive force, as well as the buckling instability of the originally helical filament that occurs above a critical rotation velocity. A sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 45 publications
2
58
0
Order By: Relevance
“…Because the resultant drag from the cell body exactly balances the propulsive force, the hook is under tension for pullers and under compression for pushers. Experiments with both elastic and rigid flagella have shown that the hook will buckle under large enough compression, one consequence being misalignment between the cell body and flagellum (3,6). Buckling has been observed in Vibrio alginolyticus when the hook unwinds and significantly weakens during a pull-to-push transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the resultant drag from the cell body exactly balances the propulsive force, the hook is under tension for pullers and under compression for pushers. Experiments with both elastic and rigid flagella have shown that the hook will buckle under large enough compression, one consequence being misalignment between the cell body and flagellum (3,6). Buckling has been observed in Vibrio alginolyticus when the hook unwinds and significantly weakens during a pull-to-push transition.…”
Section: Introductionmentioning
confidence: 99%
“…Because assigning configurations to swimmers necessarily precludes the exploration of any hook dynamics or mechanics, other studies instead use various models incorporating elasticity to examine the stability of the hook and of the overall flagellar filament (12)(13)(14)(15). Indeed, models of a standalone elastic flagellum show instability in the equilibrium helical shape above a critical applied torque load/angular velocity (6,14). However, for flagella attached to cell bodies, experiments show that the hook can buckle even without significant deformation to the flagellar filament, highlighting the key role the local hook flexibility plays in determining the stability of swimming (3).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the instability is localized at the highly compliant hook that connects the slender flagellum to the rotary motor inside the cell body. Subsequently, by combining computer simulations and precision model experiments, we have demonstrated [25] that it is possible for the actual flagella to buckle, itself a helical filament that is highly flexible ought to its slenderness. Here, the instability arises due to the compressive stresses that derive from the viscous loading during the rotation of the helical filament.…”
Section: Introductionmentioning
confidence: 99%
“…In all these cases, the flexible body experiences shape reconfiguration with self-streamlining and reduction of the surface area exposed to the flow, thus resulting in a drastic reduction of the drag force exerted on the object [10]. An immediate field of application of these problems can be found in bio-physical domains, when a passive or an active elastic part of a body interacts with the flow [6,[11][12][13]. In particular, in animal locomotion, the flexibility of wings or fins intervene in the flying of birds and insects or the swimming of fishes or eels.…”
Section: Introductionmentioning
confidence: 99%